Effects of real and financial variables on the yield curve of sovereign bonds in soles - Chávarri Balladares, Albert Farith (2022)
Objective: Analyze the effects of real and financial variables on the yield curve of sovereign bonds in soles for the period January 2008 – September 2022. Method: By using the Piecewise Cubic Hermite Interpolating Polynomial interpolation method, the zero coupon curve was estimated, which is broken down into unobservable factors (level, slope and curvature) using a principal component model; subsequently, these factors were exposed to shock variables through a Structural Factor Augmented Vector Autoregressive. Results: There are changes in the US monetary policy rate or increases in the financial volatility, which have an impact on the entire yield curve; besides, an increase in the GDP variation rate, in inflation or in the exchange rate affects the level of the yield curve in a negative way; while a negative shock in the monetary policy rate increases the level and slope of the yield curve. Conclusion: External variables and the decisions of the Central Bank affect significantly the yield curve.